1977
DOI: 10.3177/jnsv.23.115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of limiting amino acids on tyrosine toxicity in rats fed wheat gluten diets.

Abstract: SummaryThe effect of supplementation of limiting amino acids on rats fed a 10 or 20% wheat gluten diet containing 5% tyrosine has been investigated. Growth-limiting amino acids in a 20% wheat gluten diet were lysine and threonine. When rats were fed a 20% wheat gluten diet containing excess tyrosine, the addition of 1.0% lysine• HC1 or 1.0% lysine• HC1 and 0.4% threonine completely prevented the development of tyrosine toxicity, and was accompanied by a lowering of free tyrosine concentrations in plasma, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…That free tyrosine concentration in tissues increases greatly in rats fed a high tyrosine diet but decreases in animals fed a high tyrosine diet containing additional protein or some amino acids has been well demon strated. 5,8,14,18,19,24,25) Results of Experiment 2 showed that not only addition of extra casein but also methionine and threonine has a great effect on lowering free tyrosine concentrations. These data indicate clearly that there exists a high correlation between tyrosine concentra tion in body fluids and development of tyrosine toxicity, and also suggest that the main sub stance responsible for tyrosine toxicity is tyrosine itself.…”
Section: Discussionmentioning
confidence: 99%
“…That free tyrosine concentration in tissues increases greatly in rats fed a high tyrosine diet but decreases in animals fed a high tyrosine diet containing additional protein or some amino acids has been well demon strated. 5,8,14,18,19,24,25) Results of Experiment 2 showed that not only addition of extra casein but also methionine and threonine has a great effect on lowering free tyrosine concentrations. These data indicate clearly that there exists a high correlation between tyrosine concentra tion in body fluids and development of tyrosine toxicity, and also suggest that the main sub stance responsible for tyrosine toxicity is tyrosine itself.…”
Section: Discussionmentioning
confidence: 99%